2019
DOI: 10.1073/pnas.1815354116
|View full text |Cite
|
Sign up to set email alerts
|

In vivo selective inhibition of TRPC6 by antagonist BI 749327 ameliorates fibrosis and dysfunction in cardiac and renal disease

Abstract: Transient receptor potential canonical type 6 (TRPC6) is a nonselective receptor-operated cation channel that regulates reactive fibrosis and growth signaling. Increased TRPC6 activity from enhanced gene expression or gain-of-function mutations contribute to cardiac and/or renal disease. Despite evidence supporting a pathophysiological role, no orally bioavailable selective TRPC6 inhibitor has yet been developed and tested in vivo in disease models. Here, we report an orally bioavailable TRPC6 antagonist (BI 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 44 publications
5
111
0
Order By: Relevance
“…Most of the TRPC channels, TRPC1, TRPC3, TRPC6, TRPC7, and the heterotetrameric channel complexes TRPC3/6/7, TRPC1/4/5, and TRPC1/TRPC4 [202], have been demonstrated to be important mediators of pathological hypertrophy, and may serve as therapeutic targets [201,203]. Indeed, the TRPC3 blocker Pyrazole-3 (Pyr3) [166], the combined TRPC3 and TRPC6 channel blockers GSK2332255B and GSK2833503A [204], and the TRPC6 channel blocker BI-749327 [38], are effective at attenuating pathological remodeling and improving heart function. Although these studies provide strong evidence that TRPC channels in cardiac myocytes play an essential role in mediating hypertrophic remodeling, it remains unclear whether TRPC channels in cardiac fibroblasts contribute to pathological remodeling.…”
Section: Trpc Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the TRPC channels, TRPC1, TRPC3, TRPC6, TRPC7, and the heterotetrameric channel complexes TRPC3/6/7, TRPC1/4/5, and TRPC1/TRPC4 [202], have been demonstrated to be important mediators of pathological hypertrophy, and may serve as therapeutic targets [201,203]. Indeed, the TRPC3 blocker Pyrazole-3 (Pyr3) [166], the combined TRPC3 and TRPC6 channel blockers GSK2332255B and GSK2833503A [204], and the TRPC6 channel blocker BI-749327 [38], are effective at attenuating pathological remodeling and improving heart function. Although these studies provide strong evidence that TRPC channels in cardiac myocytes play an essential role in mediating hypertrophic remodeling, it remains unclear whether TRPC channels in cardiac fibroblasts contribute to pathological remodeling.…”
Section: Trpc Channelsmentioning
confidence: 99%
“…Increasing the differentiation of fibroblasts is, therefore, essential for initiating and perpetuating the fibrogenesis cascade [28][29][30][31][32][33][34] and the formation of fibrosis, which is involved in various pathological cardiac remodeling processes [9,35] (Figure 1). Numerous signaling pathways are involved in the activation of cardiac fibrogenesis [36], among which intracellular Ca 2+ has been found to play a particularly critical role [37][38][39]. The Ca 2+ signaling mechanisms in cardiac fibroblasts, however, are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study, Wu et al found that TRPC6 knockout provided partial protection from renal fibrosis in mice subjected to UUO, and a comparable beneficial effect was observed in obstructed kidneys following treatment with the non-selective TRPC inhibitor BTP2 [76]. Moreover, a similar beneficial effect was observed by another group in a mouse UUO model using the selective TRPC6 inhibitor BI-749327 [166]. In the Wu et al study, the authors also examined the effects of soluble klotho in the UUO model on the basis of the following observations: (1) the investigators had previously demonstrated that soluble klotho inhibits TRPC6 exocytosis and TRPC6 currents in the heart [167], and (2) treatment with soluble klotho inhibits renal fibrosis in obstructed kidneys [168].…”
Section: Targeting Trpc Family Members In Other Acquired Kidney Diseasesmentioning
confidence: 68%
“…The contribution of TRPC6 to the compound 48/80-evoked current was elaborated by genetic deletion of TRPC6 expression. The deduced concept of TRPC6 as an indispensable constituent of cation channels activated by compound 48/80 in PMCs could be corroborated in future studies by experimental evidence showing that acute blockage of these currents using TRPC6-specific antagonists such as Pyrazolo [1,5-a] pyrimidines antagonist (62) or BI 749327 (63).…”
Section: Contribution Of Trpc Channels To Mrgprb2-mediated Ca 2+ Risementioning
confidence: 75%